The Addition of Dydrogesterone after Frozen Embryo Transfer in Hormonal Substituted Cycles with Low Progesterone Levels - Jose Metello; Claudia Tomas; Pedro Ferreira; Samuel Santos-Ribeiro (Federação Brasileira das Sociedades de Ginecologia e Obstetrícia, 2023)
Abstract Objective To determine whether a rescue strategy using dydrogesterone (DYD) could improve the outcomes of frozen embryo transfer cycles (FET) with low progesterone (P4) levels on the day of a blastocyst transfer. Methods Retrospective cohort study including FET cycles performed between July 2019 and October 2020 following an artificial endometrial preparation cycle using estradiol valerate and micronized vaginal P4 (400 mg twice daily). Whenever the serum P4 value was below 10 ng/mL on the morning of the planned transfer, DYD 10 mg three times a day was added as supplementation. The primary endpoint was ongoing pregnancy beyond 10 weeks. The sample was subdivided into two groups according to serum P4 on the day of FET: low (< 10 ng/mL, with DYD supplementation) or normal (above 10 ng/mL). We performed linear or logistic generalized estimating equations (GEE), as appropriate. Results We analyzed 304 FET cycles from 241 couples, 11.8% (n = 36) of which had serum P4 below 10 ng/mL on the FET day. Baseline clinical data of patients was comparable between the study groups. Overall, 191 cycles (62.8%) had a biochemical pregnancy, of which 131 (44,1%) were ongoing pregnancies, with a 29,8% miscarriage rate. We found no statistically significant differences in the hCG positive (63 vs 64%) or ongoing pregnancy rates (50 vs 43,3%) between those FETs with low or normal serum P4 values, even after multivariable logistic regression modelling. Conclusion Our results indicate that DYD 10 mg three times a day administered in women who perform FET with P4 serum levels < 10 ng/mL, allows this group to have pregnancy rates beyond 12 weeks at least as good as those with serum levels above 10 ng/mL.